RETROFIT DE EDIFÍCIOS: UMA REVISÃO SISTEMÁTICA DA LITERATURA - Melo, Adriana V. S.; Ferreira, Emerson A. M.; Costa, Dayana Bastos (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The retrofit is challenge investment with high cost, significant technical uncertainty, and inaccurate deadlines. This paper proposes to identify the retrofit evolution in relation to buildings future. The systematic review of the literature was used to search and select publication in the Scopus Database and Database Thesis and Dissertations of the Coordination of Improvement of Higher Education Personnel (CAPES). The keywords select involved the words "framework" retrofit , building future and design retrofit and in the Brazil rehabilitation. The findings indicate that the first publications aimed at reducing deterioration of buildings and elimination the obsolescence of building for aesthetic improvement and the quality of the air internal, in addition to cost-effectiveness. In the current tendency of the studies lead to the reduction of existing fragilities, to building resilience, with adaptability and less vulnerability. The current interest is the reduction of primary energy consumption of the existing and futures buildings, highlighting the quality of indoor air, followed by the building envelope and the evaluation of the user's behavior.